Surgical Approach to Primary Hyperparathyroidism in Patients with Concomitant Thyroid Diseases: A Retrospective Single Center Study - Elena Castellano; Paolo Benso; Roberto Attanasio; Alberto Boriano; Corrado Lauro; Giorgio Borretta; Felice Borghi (International Journal of Endocrinology)
Background. Primary hyperparathyroidism (PHPT) and thyroid diseases are a frequent concomitant occurrence, but the surgical approach to associated disease is still debated. Methods. We retrospectively evaluated a series of PHPT patients focusing on thyroid disease and surgery. Results. Among 238 PHPT patients undergoing parathyroidectomy (PTX) between 2002 and 2017, 128 were affected also by a benign thyroid disease, namely, goiter in 118 (76 multinodular (MNG) and 42 uninodular (UNG)), autoimmune thyroiditis in 10, and hyperthyroidism in 21. Surgical approach was unilateral neck exploration (UNE) in 59 patients and bilateral neck exploration (BNE) in 69. The PHPT cure rate was 94%. On comparing patients submitted to PTX only and PTX plus thyroidectomy (TX), in the latter MNG and hyperthyroidism were more frequent, and surgical time and length of stay were longer. No difference in surgical complications was found between patients undergoing UNE and BNE. Conclusion. PHPT patients with a concomitant thyroid disease underwent double surgery in almost two-thirds of the cases, mostly by BNE. The main factors driving the decision to perform concomitant PTX and TX were the presence of thyroid nodular disease with the nodule site ipsilateral to the presurgically localized parathyroid adenoma.